The Effect of the Debt to Equity Ratio (DER), Return on Assets (RoA), and Current Ratio (CR) on Firm Value (in the Coal Subsector of Companies Listed on the Indonesia Stock Exchange, 2018–2024) - Dhita Alifia Herdiana; Kasir Kasir; Devyanthi Syarif; Tjipto Sajekti (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to analyze the effect of ROA, DER, and CR on PBV in the coal sector for the period 2018-2024. The analysis uses panel data regression with the CEM method. The results show that, partially, ROA has no significant effect on PBV; DER shows a negative and significant effect on PBV; and CR shows no effect on PBV. However, simultaneously, ROA, DER, and CR were found to influence PBV. These findings indicate that although not all variables have a partial effect, the combination of profitability, leverage, and liquidity still plays a significant role in explaining variations in firm value. This study contributes to the knowledge of investors and management in considering the fundamental factors that influence a company's market value.